CONCENTRATION OF NICKEL (Ni) AND CHROMIUM (Cr) lN SEDIMENT AND SUSO SNAIL (Tylomelania patriarchalis) AT BOTTOM LAYER OF MATANO LAKE, SOUTH SULAWESI - Kamaluddin Kasim; Mas Tri Djoko Sunarno (Indonesian Fisheries Research Journal, 2009)
Research on nickel (Ni) and chromium (Cr) concentration in sediment and meat of suso snail (Tytometania patriarchatis) collected from bottom layer of Lake Matano, South Sulawesi, was conducted on July-August 2004. Research station was established purposively according to a distance from source of industrial activities, namely station A (25 km), station B (14 km), station C (5 km), and station D (7 km), respectively.